1989
DOI: 10.1113/jphysiol.1989.sp017840
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral regulation of renal sodium excretion in sheep infused intravenously with hypertonic NaCl.

Abstract: SUMMARY1. The natriuretic response to intravenous infusion of 2 M-NaCl was investigated in six conscious sheep. This hypertonic NaCl load resulted in relatively small, physiological (2-3 mmol 1-1) increases in plasma Na+ concentration and was followed by a natriuresis with a maximum mean urinary sodium excretion 5 times higher than pre-infusion values.2. Intravenous infusion of isotonic NaCl, delivering the same Na+ load as hypertonic NaCl infusion, did not induce natriuresis. This suggested, therefore, that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Over the years a number of experimental results have suggested that the concentration of Na+ presented to the central nervous system (CNS) either from the blood or from the cerebrospinal fluid may participate in the regulation of renal Na+ excretion (Andersson et , Chodobski & McKinley 1989, Emmeluth et al 1992. However, it is still a Correspondence : Claw Emmeluth, Department of Medical Physiology, University of Copenhagen, 3 Blegdamsvej, DK-2200 Copenhagen N, Denmark.…”
mentioning
confidence: 99%
“…Over the years a number of experimental results have suggested that the concentration of Na+ presented to the central nervous system (CNS) either from the blood or from the cerebrospinal fluid may participate in the regulation of renal Na+ excretion (Andersson et , Chodobski & McKinley 1989, Emmeluth et al 1992. However, it is still a Correspondence : Claw Emmeluth, Department of Medical Physiology, University of Copenhagen, 3 Blegdamsvej, DK-2200 Copenhagen N, Denmark.…”
mentioning
confidence: 99%
“…1992). Preventing CSF sodium concentration from increasing during intravenous infusion of hypertonic saline infusion, or postprandially, also blocks the natriuretic responses following intravenous hypertonic saline or feeding (Chodobski & McKinley 1989, McKinley et al . 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary Na retention ensued body fluid dilution by means of rehydration in a dehydrated animal (21). A hypertonic NaCI intravenous load resulted in a compensating natriuresis (8). A severe antinatriuretic response was produced by a water load ( 14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the ventriculocisternal perfusion with isosmotic low-sodium solution or hyposmotic low-sodium solution produced a notable decrease of the renal Na output (25), an increase in plasmatic Na concentration, and excessive loss of water (8). Furthermore, the natriuresis induced by an intravenous hypertonic NaC1 load could be blocked by lowering the cerebrospinal fluid Na concentration (8). Finally, the natriuresis observed in normal sheep after water deprivation (22) or after intravenous infusion of hypertonic saline (19) was blocked by ablation of the anterior third ventricle.…”
mentioning
confidence: 82%
See 1 more Smart Citation